Family Criminology: An Introduction - Holt, Amanda (Springer eBook Collection, 2021)
1. Introduction -- 2. The Criminogenic Family: Families As The Cause Of Crime In Research And Policy -- 3. The Stigmatised Family: The Impact Of Offending On Families -- 4. The Mafia Family: Organised Crime Families -- 5. The Violent Family: Domestic And Family Violence -- 6. The Homicidal Family: The Killing Of Family Members -- 7. The Traumatised Family: The Families Of Victims -- 8. The Campaigning Family: Victims’ Families Transforming Justice -- 9. Discussion -- 10. Key Terms.